Does city-county merger improve urban carbon emission efficiency? An empirical analysis based on the difference-in-differences model - Fan, Xuechen; Xu, Shuhua (Frontiers in Sustainable Cities, 2025)
The enhancement of carbon emission efficiency (CEE) in urban areas is essential for alleviating the negative impacts of climate change and promoting sustainable urban development. Nonetheless, there is no evidence to suggest that any specific spatial optimization technique significantly impacts urban spatial structure and CEE. The administrative boundary adjustment (ABA) functions as an effective instrument for hierarchical network governance in China, possessing the capacity to accomplish this objective through its redistributive impact on urban spatial resources. Thus, we utilize the “City-County Merger” (CCM)–a standard ABA policy to investigate its environmental impacts based on the mediation mechanism of urban spatial structure. The empirical findings derived from a panel dataset encompassing 285 Chinese cities and the Difference-in-Differences model (DID) indicate that the CCM will significantly enhance the CEE of urban regions. This effect is particularly pronounced in mid-western, northwestern, lower administrative level, and non-resource-based cities. The mediation mechanisms suggest that the environmental benefits of CCM in China arise from the optimization of urban spatial organization, which enhances CEE by fostering urban polycentricity and compactness. The supplementary spatial econometric analysis results demonstrate that implementing the CCM policy has a significant spatial spillover effect on the enhancement of CEE.